WONOEP APPRAISAL: The many facets of epilepsy networks - Scott, Rod C.; De La Prida, Liset Menendez; Mahoney, J. Matt; Kobow, Katja; Sankar, Raman; De Curtis, Marco (Epilepsia, 2018)
The brain is a complex system composed of networks of interacting elements, from genes to circuits, whose function (and dysfunction) is not derivable from the superposition of individual components. Epilepsy is frequently described as a network disease, but to date, there is no standardized framework within which network concepts applicable to all levels from genes to whole brain can be used to generate deeper insights into the pathogenesis of seizures or the associated morbidities. To address this shortcoming, the Neurobiology Commission of the International League Against Epilepsy dedicated a Workshop on Neurobiology of Epilepsy (XIV WONOEP 2017) with the aim of formalizing network concepts as they apply to epilepsy and to critically discuss whether and how such concepts could augment current research endeavors. Here, we review concepts and strategies derived by considering epilepsy as a disease of different network hierarchies that range from genes to clinical phenotypes. We propose that the concept of networks is important for understanding epilepsy and is critical for developing new study designs. These approaches could ultimately facilitate the development of novel diagnostic and therapeutic strategies.
EVALuna2:36568